(untitled) (Journal of Nepal Physical Society, 2024)
Testosterone is a steroid sex hormone that regulates sex differentiation, male sex characteristics, spermatogenesis and fertility. It also functions in carbohydrate, lipid, and protein metabolism. It is largely produced by the male gonad and a variety of female organs. A lack of testosterone hormone can cause in increased fat mass, reduced insulin action, and undesirable cholesterol deposition in the body. The concentration of this hormone might vary even within healthy human. A protein, anti-testosterone Fab fragment antibody, has been proposed as the binding molecule that can maintain the hormone appropriately in our body. In this study, we investigated the binding of testosterone hormone to light and heavy chains of antibody and compared the binding strength by utilizing various binding methods, hydrogen bonding, non-bonded contact, and binding free energy estimation. The results of molecular dynamics simulation demonstrate that testosterone hormone binds more strongly to the heavy chain than the light chain. The strongest hydrogen bonding in atom pairs has been found to be between the O2 atom of testosterone and the O atom of GLY104 in heavy chain of antibody molecule, while the others were substantially weaker. Non-bonded interactions (electrostatic and van der Waals) play a crucial role in the formation of the protein-hormone complex. The MM/GBSA approach reveals that the binding energy of testosterone and heavy chain pairs is - 18.27 kcal/mol, which is almost three times greater than that of testosterone and light chain pairs - 6.60 kcal/mol.